Business Strategy of Cattle Farmers and Bottleneck in Production Under The Rise in Beef Price: A Case Study in Malang District - Laila, Nuning Nur; Wijaya, Andy Fefta; Amin, Fadillah (Jurnal Ilmiah Administrasi Publik, 2017)
A survey of thirteen farmers using qualitative method with in-depth interview was carried out in Malang District in order to observe farmers’ constraints and the strategy taken under the rise in beef price. The result showed that during 2010-2015, Malang District farmers had faced constraints such as difficulty in accessing cattle, poor feeding behavior, and long selling channel. Most of them had joinedcattle sharing system in order to access cattle. Based on trust and kinship, cattle sharing system allowed smallholders to gain access to the cattle. On the other hand, some farmers’ showed their interest joining farmer group in order to improve their poor feeding behavior. Farmer group could be a good solution to enhance farmers’ skill in rearing cattle with good guidance. Selling carcass to the beef seller will give higher profit to the farmer, but it has some constraints such as need particular skill to be butcher, needs government license, takes time and need a market link. This new market access must be observed further to know it’s potential.